Hydrogen-bonding-mediated structural stability and electrochemical performance of iron fluoride cathode materials. Issue 31 (21st August 2015) - Li, Zuosheng; Wang, Beizhou; Li, Chilin; Liu, Jianjun; Zhang, Wenqing
<x xml:space="preserve">Abstract</x> Tunable H2O–F− hydrogen bonding is crucial to the structural stability and electrochemical performance of FeF3·0.33H2O cathode materials.